2022
DOI: 10.19163/1994-9480-2022-19-4-34-49
|View full text |Cite
|
Sign up to set email alerts
|

Modern Concepts of the Pathogenesis of Type 2 Diabetes Mellitus

Abstract: Resume. In Russia, type 2 diabetes affects more than 5 % of the population. Type 2 diabetes accounts for up to 95 % of all cases of diabetes meUitus, but its pathogenetic mechanisms have not yet been fully established. Aim. To summarize and analyze the Literature data on the pathogenetic Links of type 2 diabetes mellitus. Materials and methods. When searching for material for writing a review article, abstract databases PubMed, Google Scholar, e-Library, etc. were used. The search was carried out by publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Additionally, it may reduce basal hyperinsulinemia, improve insulin sensitivity, and preserve beta‐cell function and mass. Studies have shown that systemic infusion of AICAR can prevent the development of hyperglycemia and maintain prediabetic beta‐cell mass 7,37 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it may reduce basal hyperinsulinemia, improve insulin sensitivity, and preserve beta‐cell function and mass. Studies have shown that systemic infusion of AICAR can prevent the development of hyperglycemia and maintain prediabetic beta‐cell mass 7,37 …”
Section: Introductionmentioning
confidence: 99%